Analysis of the Practicality of HOTS-based Inquiry Training Model in Vocational Training - Aminuddin , Rosihan; Syahrul, Syahrul; Andi Muhammad Idkhan (Cita konsultindo, 2024)
The HOTS-based inquiry training model is a learning approach designed to develop higher-order thinking skills, such as analysis, evaluation, and creation, through the process of exploration and problem-solving. The purpose of this study is to find out the practical picture of the HOTS-based inquiry training model. This type of research is a quantitative research with a survey approach. The implementation of the trial was carried out in three stages, namely small, limited, and field trials. The data collection technique is carried out by: (1) observing lecturers carrying out training using a HOTS-based inquiry training model on electrical expertise competencies; (2) ask for a response or response from lecturers after using the HOTS-based inquiry training model. The results of this study were obtained: (1) The implementation of the training model during the implementation of small group, limited group, and field trials show that observers consistently give assessments in the very practical category; (2) Products have good validity, reliability, objectivity, and practicality, with the best test results seen on the field scale.